China’s Fiscal Decentralization: consequences for the promotion of local development - Carrillo García, Beatriz (México y la Cuenca del Pacífico, 2015)
Fiscal decentralization has been an integral part of China’s decentralization process, which successfully promoted local government entrepreneurialism. But while fiscal reform gave governments increasing authority over local revenue, they have also faced increasing expenditure responsibilities. This article aims to analyze the processes of fiscal decentralization that was put in place in the early 1980s, and to elucidate on the rationale and consequences of that process. Resumen: La descentralización fiscal ha sido parte integral del proceso más general de descentralización en China, que ha promovido exitosamente el emprendedurismo del gobierno local. Sin embargo, mientras la reforma fiscal les dio a los gobiernos locales mayor control sobre sus ingresos, al mismo tiempo estos han enfrentado mayores responsabilidades en el gasto. Este artículo se propone analizar el proceso de descentralización fiscal que se llevó a cabo a partir de los ochenta y elucidar la racionalización y las consecuencias de ese proceso.